PREDICATED THEMES IN A LITERARY CORPUS: THEIR USE AS TEXTUAL RESOURCE IN ALAN PATON’S CRY, THE BELOVED COUNTRY (1948) - Lirola, María (POLISSEMA – Revista de Letras do ISCAP, 2013)
This article will show how the frequency of a grammatical structure such as the predicated theme in the novel Cry, the Beloved Country (1948) written by the South African writer Alan Paton is crucial for the meaning of the novel. The usefulness of this marked construction for textual cohesion and contrastiveness will be explored. Special attention will be paid to the discourse functions of the examples in order to observe the consequences of this grammatical choice in the novel: to highlight, contrast, emphasize feelings, etc. The use of predicated themes in this novel allows Paton not only to make the text a more coherent unit – a text – but also allows him to draw the text closer to the context of the situation of the reader, drawing the reader ‘into’ a ‘dialogue’ with the issues of the culture of the time, into the ‘cultural dialogue’ of Apartheid South Africa – the dialogue of the black and the white South Africans.